Growth of anisotropic single crystals of a random copolymer, poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate] driven by cooperative –CH···O H-bonding. (10th October 2018) - Liu, Changhao; Noda, Isao; Martin, David C.; Chase, D. Bruce; Ni, Chaoying; Rabolt, John F.
Abstract: Single crystals of a random copolymer, Poly[(R)-3-hydroxybutyrate- co -(R)-3-hydroxyhexanoate] (PHBHx), with a relatively high (R)-3-hydroxyhexanoate (3HHx) content of 3.9 mol% were grown from dilute solutions over a wide range of crystallization temperatures ( T c ) from −20 °C to 75 °C. Unlike Poly[(R)-3-hydroxybutyrate- co -(R)-3-hydroxyvalerate] (PHBV) which allows the 3-hydroxyvalerate (3HV) to be included into PHB lattice, 3HHx is excluded from the lattice as a non-crystallizable molecular defect. Remarkably, however, even at such a high defect content, all the samples (except for T c = −20 °C) formed well-developed needle-shaped single crystals, with a crystal morphology similar to that found for crystals of the homopolymer PHB. A very characteristic anisotropic lateral growth habit is observed, with the growth rate along the a axis being much higher than that along the b axis. This anisotropic growth pattern was significantly enhanced at T c = 20 °C, wherein the unit cell packing velocity along the a direction is approximately 55 times faster than that along the b direction. This thermal dependent anisotropy was attributed to an unusual cooperative hydrogen bond-like network formed by methyl hydrogen and a neighboring carbonyl oxygen in the α crystal of PHB. Another manifestation of this H-bonding network can be seen in unusually thin crystal lamellae at −20 °C, with only ∼6 repeat units per stem, suggesting a superior stability of crystal structure. Interestingly, at this temperature, although 3HHx still cannot be accommodated along the a direction (the H-bonding direction), it could be included along the b direction, indicated by the observation of lattice expansion along the b direction. Also at T c = −20 °C, we found that 3HHx began to show some impact on the crystalline morphology, indicated by the development of a twisted lamellar texture. This effect was believed to arise from the release of stress induced by a congested fold surface dominated by non-crystalline 3HHx and 3HB units. Graphical abstract: Highlights: Single crystals of a random copolymer, PHBHx, with 3.9 mol% of 3HHx were grown. The 3HHx comonomer is excluded from the lattice as a non-crystallizable defect. All samples grown at different T c formed well-developed needle-shaped single crystals. A very anisotropic lateral growth habit of the single crystals was observed. The growth rate along a axis was observed to be much higher than that along the b axis.